Influence of servicescape on behavioural intentions through mediation and moderation effects: A study on Malaysiaâs full-service restaurants - Asghar Ali, M. (Cogent OA, 2021)
Restaurant servicescape domain consists of physical and social aspects. Surprisingly, both aspects have been studied independently. This study aims to investigate the unanimous effects of servicescape on consumer behaviour in a full-service context (Malaysia) through the mediating and moderating effects of customer satisfaction and perceived crowding. Online survey method was used for data collection. 300 respondents completed and returned the questionnaire. Only 200 properly filled responses were subjected to data analysis using the Smart PLS-SEM technique. Based on the results, servicescape (3rd order construct) directly influenced eWOM and repurchase intentions. An indirect effect through partial mediation of customer satisfaction was also found. Furthermore, perceived crowding positively moderated the relationship between servicescape and customer satisfaction. Limited number of studies have investigated the holistic effects of servicescape on consumption evaluation and consumer behaviour. This is the first study on full-service restaurant context, investigating servicescape as a higher-order construct. Full-service restaurants need to be conscious of servicescape elements to maintain an acceptable level of crowding and to positively influence consumer behaviour. Â© 2021 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.